The structure of Albanian personality descriptive trait-adjectives: A psycho-lexically based taxonomy - Rudina Ademi Shala; Boele De Raad; Aliriza Arënliu (International Journal of Personality Psychology, 2020)
In this study, we describe the taxonomy of personality descriptive trait terms in the Albanian language according to the psycho-lexical procedure, in two parts. In the first part the selection of trait terms from a standard Albanian dictionary took place, largely according to standard procedures. This resulted in a useful set of 607 personality relevant terms. In the second part this list of trait terms was administered to 497 participants to obtain self-ratings. During the rating process, participants could indicate their familiarity with the terms, leading to another reduction to a final set of 434 trait terms with self-ratings. Principal Components Analysis followed by Varimax rotation was applied both using raw data and using ipsatized data. Structures with one up to seven factors were discussed and represented in a hierarchy of factor solutions. As an aid to the interpretation of the factors, use was made of markers of the Big Five, selected from the full list of 434 terms. The most comprehensive and clearest structure was found with seven factors, which included the Big Five and both Negative Valence and Positive Valence.